How RAG1/2 evolved from ancestral transposases to initiate V(D)J recombination without transposition - Xuemin Chen; Liangrui Yao; Wenwen Li; Shanshan Ma; Xingyun Yuan; Yang Yang; Yuan Yuan; Yumei Liu; Lan Liu; Huaibin Wang; Martin Gellert; Wei Yang (Proceedings of the National Academy of Sciences, 2025)
The recombination activating genes 1 and 2 (RAG1/2) recombinase, which initiates V(D)J recombination in jawed vertebrates, evolved from RNaseH-like transposases such as Transib and ProtoRAG. However, its postcleavage transposase activity is strictly suppressed. Previous structural studies have focused only on the conserved core domains of RAG1/2, leaving the regulatory mechanisms of the noncore regions unclear. To investigate how RAG1/2 suppresses transposition and regulates DNA cleavage, we determined cryo-electron microscopy (cryo-EM) structures of nearly full-length RAG1/2 complexed with cleaved recombination signal sequences (RSS) in a signal-end complex (SEC) at resolutions up to 2.95 Å. Two key structures, SEC-0 and SEC-Plant Homeodomain (PHD), reveal distinct regulatory roles of RAG2, which is absent in Transib transposase. SEC-0 displays a closed conformation, revealing that the core RAG2 facilitates sequential DNA cleavage by stabilizing the RSS-cleaved states in a “spring-loaded” mechanism. SEC-PHD reveals how RAG2’s noncore PHD and Acidic Hinge (AH), which are absent in ProtoRAG, inhibit target DNA binding in transposition. Histone H3K4me3, which recruits RAG1/2 to RSS sites, does not influence RAG1/2 binding to V, D, or J gene segments bordered by RSS. In contrast, the suppressed transposition can be activated by H3K4me3 peptides that dislodge the inhibitory PHD. To achieve this derepression in vivo, however, would require an unlikely close placement of two nucleosomes flanking a target DNA bent by nearly 180°. Our structural and biochemical results elucidate how RAG1 has acquired RAG2 and utilizes its core and noncore domains to enhance V(D)J recombination and suppress transposition.